Investigation of the intermediate layers formed by austenitic nitrocarburising. (2016) - GodzsÁ¡k, Melinda; Pekker, Péter; Cora, Ildikó; Veres, Zsolt
By nitriding the Fe-N system above the eutectoid temperature (592°C), an intermediate layer called (nitro)austenite is formed under the compound layer that can transform into braunite during low-rate cooling at eutectoid temperature. The two-phase complement of structure forming such a way - namely the braunite - is an eutectoid consisting of body-centred cubic α-iron and Fe4 N iron-nitride compound (α + γ´). This poorly investigated texture and its formation was investigated. During our experiments, 100Cr6 and C105U steels were nitrocarburised above the eutectoid temperature (592°C). The conditions and properties of the formation of the developed intermediate layers, the microstructure and the distribution of the nitrogen and carbon in the specimens were investigated by using light optical microscopy (LOM), microhardness measurements, X-ray diffraction (XRD) method, scanning (SEM) and transmission (TEM) electronmicroscopy and glow discharge optical emission spectrometry (GD-OES).